Modelling the inhibitory effect of LAB on L. monocytogenes and Enterobacteriaceae in a fermented sausage during ripening - Cadavez, Vasco (2017)
Earlier research has shown that the survivability of Enterobacteriaceae (ENT) and L. monocytogenes (LM) in a Portuguese fermented sausage (linguiça) decreases during the ripening stage, and that such inhibition arises from the adverse conditions caused by the competition with autochthonous lactic acid bacteria (LAB) and the progressively lower water activity and pH. The objective of this work was to mathematically characterise the competition or interactions between LAB, LM and ENT that takes place in fermenting linguiça during ripening.